The Effect of Bromfenac Sodium Nanopolymer Used in Anterior Segment of the Eye on Corneal Neovascularization: Bromfenac Sodium Nanopolymer and Corneal Neovascularization - Song, Li; Liu, Xiao; Chen, Nan; Liu, Jiayan; Nie, Aiqin; Li, Wei (Cellular and Molecular Biology, 2022)
This study was to explore the inhibitory effect of bromfenac sodium (BF) / chitosan (CS) nanoparticles (NPs) on corneal neovascularization (CNV). 45 New Zealand white rabbits provided by The First Affiliated Hospital of Jinan University were randomly divided into a control group (group A, n = 15), 0.1% BF aqueous solution treatment group (group B, n = 15), and 0.1% BF/CS-NPs suspension treatment group (group C, n = 15). A rabbit corneal alkali burn model was established. The average particle size of BF/CS-NPs with different BF concentrations was mainly 341.6 ± 12.9 nm - 548.7 ± 15.4 nm; and the Zeta potential distribution was 24.3 ± 2.5 mV - 35.7 ± 4.3 mV. When the initial concentration of BF was 1.5 mg/mL, the maximum drug loading was 57.35 ± 5.26%. The area of CNV in group C was significantly lower than that in groups B and A, and the differences were statistically significant (P < 0.05). At 6, 12, 18, and 24 days after surgery, the mRNA expression levels in cyclooxygenase-2 (COX-2) and vascular endothelial growth factor (VEGF) gene were compared after standardized by β-actin; group A had the highest expression level, followed by group B, and group C had the lowest expression level, showing statistically significant differences (P < 0.05). The BF/CS-NPs granules prepared in this study had stable physical and chemical properties and had a good sustained-release effect, and the release duration can be as long as 48 hours. BF/CS-NPs can inhibit the formation of CNV at different time points after alkali burn, and reduce the expression of VEGF and COX-2 in corneal tissue after alkali burn.